Training Needs among KAFA Teachers: A Case Study in Selangor - Mohd Salleh, Hamdan; Ali, Affezah; Ming Yip, Ng; Afnizul, Afina Nazira (Selangor Humaniora Review, 2021)
The role of elementary school teachers to teach religious education is increasingly crucial to deliver intensive education of the upcoming Muslim generation, specifically in a developed state like Selangor. Currently, there are 9,465 KAFA teachers teaching approximately 250,563 students in Selangor. These numbers certainly require a specific study of the training needs of these teachers. To this date, there has been no significant study that precisely addresses and discusses the training needs of the teachers. Therefore, this study was conducted to identify the training required by religious primary school teachers in Selangor to identify the gap between the existing training and the training desired and form the basis for a training plan. This study is a qualitative study and uses a focus group discussion (FGD) approach. This study involved 20 teachers teaching Islamic education from the chosen five districts in Selangor. The findings revealed that the current training could be improved in several aspects, including disability facilitations, knowledge and skill mastery in educational pedagogy, teaching and learning, leadership in education, student counselling, and consultation. This finding is specifically significant in developing a truly holistic policy in regard to religious primary schools in Selangor.